Teaching Speaking through Storytelling: a Case Study in the Tenth Grade Students of Islamic High School in Kendari - Siti Asniatih; Afaq Ahmed; Ghazanfar Iqbal; Zahid Hussain Dool; Sohail Ahmad (Journal of Language Education and Educational Technology (JLEET), 2020)
One of the major problems of many English as Foreign Language (EFL) teachers in Indonesia is particularly in their speaking classroom where most students could not take part optimally in speaking activities. This study documented the process of teaching speaking through storytelling in which students involved in their learning activities. The study aimed to describe how speaking is taught through storytelling and types of oral production that the students carried out during the process.  In this qualitative case study, data was collected through classroom observation (n=5) as a participant observer and closed and open-ended questionnaire which was administered to the students (n=31) in the context of MAN in Kendari. The study reported that teacher used learning activities before, during and after storytelling. In addition, teaching speaking through storytelling was conducted, integrated with other skills such as listening, reading and writing. The use of storytelling in the teaching of speaking enabled students not only to engage in the learning but also to get a meaningful learning experience. The analysis shows the kinds of oral production that the students carried out, extensive (monologue), transactional (dialogue), responsive, and imitative oral production during the learning. Nevertheless, it was only dominated by extensive (monologue), due to the nature of storytelling activities and the students’ limited English. With reference to the findings, it is recommended to train EFL teachers to use storytelling technique in their teaching practices.